Strategies to Empower Women Across the Globe: 100 Under 100. Issue 6 (November 2016) - Callister, Lynn Clark
Abstract : Small amounts of monetary resources can make a big difference to promote the health and safety of women and children living in poverty across the world. Our expert in global health nursing, Dr. Callister, describes a new resource on ways to help this vulnerable population that do not require vast financial means.